E-DEMOCRACY IN THE STRUCTURES OF THE STATE POWER - Кудрявцев, О.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article deals with problems connected with the development of e-government theory, and with the prospects of its introduction in Ukraine. Were clarified the basic transformations of state power as a results of the creation of a system of electronic public administration, as well as the prospects of Ukraine being into the number of states that have developed e-democracy.